TALENT ACQUISITION AS A STRATEGIC TOOL OF BUSINESS PERFORMANCE - Sajeewani Karunathilaka, K. G. Ganga (PEOPLE: International Journal of Social Sciences, 2020)
The business performance has been closely tied with the talent management strategies in the hyper-competitive and increasingly complex global economy in order to attain growth and sustain. The company which excelled in talent acquisition experienced which leads to leap up the business performance. Regardless of the size and nature of the business, all the organizations face war for talent. Hence, acquisition of right talent and making a talent pool can be the biggest challenge. This study moves forward theory of talent acquisition strategies (TAS) through the practical implication of private sector organizations in Sri Lanka. The talent acquisition strategies comprise with talent mapping (TM), talent identification (TI), talent onboarding (TO). The foremost intention of this study is to scrutinize the effect of talent acquisition strategies on business performance. The questionnaire survey was conducted for 195 HR professionals in the public sector organizations in Sri Lanka. In order to analyze data, Kolmogorov-Smirnov test was employed to test for its normality, and person correlation test was used for measuring the relationship between variables and multiple regression analysis was applied for determining the effect of variables. The results indicate that even though talent acquisition strategies are significant predictors of business performance public sector, contribution of talent acquisition to the business performance is minimal. Internal alignment between talent management strategies and Business Strategy are suggested for future research as crucial to trump organizational performance.